Profil Kemampuan Pemecahan Masalah Matematika dalam Menyelesaikan Soal Garis Singgung Lingkaran Berdasarkan Langkah Polya - Ahmad, Abtholuddin Ahmad; Arjudin, Arjudin; Novitasari, Dwi; Sridana, Nyoman (FKIP Universitas Mataram, 2024)
This research aims to determine the level and describe the characteristics of students' mathematical problem-solving abilities in solving tangent line problems based on Polya's steps. This research is a descriptive study with a quantitative and qualitative approach to further identify the problem-solving ability profiles performed by subjects based on Polya's stages. Data collection techniques used were tests and interviews. The test instrument consists of 2 items (determining the equation of a tangent line at point x1, y1 and determining the equation of a tangent line with gradient m) with explanatory answers and interview guidelines. There were 6 subjects in this study, with 2 students each in the high, medium, and low categories selected using purposive sampling technique. Data analysis techniques used both quantitative and qualitative data analysis techniques. The results of the study indicate (1) the level of problem-solving ability of students in the high and medium categories is 47.05%, and 5.9% in the low category, (2) students with high problem-solving abilities were able to solve problems according to all of Polya's steps, students with medium category were able to solve tangent line problems based on Polya's steps in understanding the problem and executing the solution only, while students with low category were only able to solve the equation of a tangent line at point x1, y1 in the problem understanding and execution stage.